Relevansi Pemikiran Karl Marx terhadap Masalah Korupsi di Indonesia dan Implementasinya dalam Kehidupan Gerejawi - Sitepu, Eder Timanta (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
Nowadays, Indonesia is experiencing a huge corruption phenomenon. This condition can be seen from various corruption cases that ensnare various circles in Indonesia. Corrupt perpetrators are not only workers who are squeezed by needs, but also economically well-established groups. Faced with this situation, it is important to find the root of the corruption problem that can raise public awareness. The public must be aware that corruption is very much eating away at the lives of the Indonesian people who are still trapped in poverty and enormous economic inequality. One of the thinkers who gave an overview of the phenomenon of corruption in Indonesia was Karl Marx. This paper aims to explore the relevance of Karl Marx's theory of alienation in analyzing the root causes of corruption in Indonesia. The research method used in this study is a qualitative approach with a literature study on Karl Marx's thoughts, especially Karl Marx's theory of Alienation. The results of this study show that the capitalist economic system that focuses on the pursuit of profit as much as possible contributes as much as possible as the cause of corruption in Indonesia. The capitalist economic system creates alienation from one's work and self. The power of money will give rise to greedy human character. In other words, Corruption based on Karl Marx's thought arose because of the capitalist economic system that was uncontrollable and created greedy human beings.